Sex- and Age-associated Effects on the Retrosplenial Cortex Following Trace Fear Learning - (:unkn) unknown (My University, 2021)
The rodent granular retrosplenial cortex (gRSC) forms reciprocal connections with the thalamus and hippocampus (Van Groen and Wyss, 1990, 1992; Sugar et al., 2011). The gRSC is well-positioned to coordinate information between higher-order brain structures to support complex forms of memory such as associative trace fear memories (Kwapis et al., 2014, 2015). Further, sex differences in fear learning and mechanisms underlying fear memories are observed in many of the brain regions implicated in trace fear learning such as the hippocampus, amygdala, and mPFC (Maren et al., 1994; Dalla et al., 2009; Gresack et al., 2009; Blume et al., 2017; Keiser et al., 2017), however, few studies have investigated sex differences in the RSC. The male gRSC has a diverse population of neuronal firing types, a likely requirement to encode complex associative memories. Cell types that are found in the rat gRSC include regular spiking (RS), regular spiking afterdepolarization (RSADP), burst firing, fast spiking, and late spiking neurons. The neuronal distribution drastically changes from the RS-dominant early adolescent to the RSADP-dominant mid-adolescent and adult gRSC. The afterdepolarization (ADP) component plays a key role in gRSC development but is also able to promote excitability and plasticity in fear-related regions (Azouz et al., 1996; Pike et al., 1999; Yousuf et al., 2020b). Thus, the first aim of this dissertation was to examine sex-dependent mechanisms underlying the ADP in RSADP neurons of the gRSC. Using whole-cell patch-clamp electrophysiology and morphological analysis, we determined that N-methyl-D-aspartate (NMDA) receptor blockers reduce the ADP in female but not male RSADP neurons. Additionally, dendritic complexity and branching is reduced in male RSADP neurons compared to male RS neurons, whereas dendritic complexity is similar in female RS and RSADP neurons. These data suggest that while NMDA receptor activity mediates the ADP in females, dendritic morphology may regulate it in males. The second aim of this dissertation used Pavlovian fear conditioning and patch-clamp electrophysiology to examine sex differences in the developmental trajectory of trace memories. Females show a positive linear trend in fear retrieval across early adolescence, mid-adolescence, and adulthood. Conversely, males exhibit a nonlinear trajectory where mid-adolescent rats have reduced fear retrieval compared to early adolescents and adults. Sex differences are noted only during early adolescence where males have stronger retrieval of trace fear compared to females. Similarly, sex differences in excitability of RSADP neurons in the gRSC are present during early adolescence, in which males fire more action potentials compared to females. Next, we investigated how fear retrieval alters distinct neuronal firing types in the male and female gRSC. In males, fear learning or exposure to novel stimuli reduces excitability of RSADP neurons in the early adolescent, mid-adolescent, and adult gRSC. However, in females, trace fear memory formation or exposure to novel stimuli suppresses excitability of both RS and RSADP neurons only in the adult gRSC. These data suggest that the male RSC is part of the trace fear circuitry early in development, whereas the female RSC may join the circuit later in development. Collectively, the results from this dissertation provide evidence that the male and female gRSC require distinct mechanisms to reach maturity, and are differentially affected by learning or novel experiences. Our work can provide insight regarding formation of maladaptive memories that underlie anxiety disorders that disproportionately affect women and adolescent girls.
Keywords: Cell-type specificity; Experience-dependent plasticity; Intrinsic excitability; Learning and Memory; Sex differences; Trace fear memories